Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine the values of [tex]\( k \)[/tex] for which the distance between the points [tex]\((-3, k)\)[/tex] and [tex]\((2, 0)\)[/tex] is [tex]\(\sqrt{34}\)[/tex], we will use the distance formula. The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here,
[tex]\[ x_1 = -3, \][/tex]
[tex]\[ y_1 = k \][/tex]
[tex]\[ x_2 = 2, \][/tex]
[tex]\[ y_2 = 0 \][/tex]
[tex]\[ d = \sqrt{34} \][/tex]
We substitute the values into the distance formula:
[tex]\[ \sqrt{34} = \sqrt{(2 - (-3))^2 + (0 - k)^2} \][/tex]
Simplify inside the square root:
[tex]\[ \sqrt{34} = \sqrt{(2 + 3)^2 + (0 - k)^2} \][/tex]
[tex]\[ \sqrt{34} = \sqrt{5^2 + (-k)^2} \][/tex]
[tex]\[ \sqrt{34} = \sqrt{25 + k^2} \][/tex]
Next, remove the square roots by squaring both sides of the equation:
[tex]\[ 34 = 25 + k^2 \][/tex]
To isolate [tex]\( k^2 \)[/tex], subtract 25 from both sides:
[tex]\[ 34 - 25 = k^2 \][/tex]
[tex]\[ 9 = k^2 \][/tex]
Now, solve for [tex]\( k \)[/tex] by taking the square root of both sides:
[tex]\[ k = \pm \sqrt{9} \][/tex]
[tex]\[ k = \pm 3 \][/tex]
Therefore, the values of [tex]\( k \)[/tex] that satisfy the condition are [tex]\( k = 3 \)[/tex] and [tex]\( k = -3 \)[/tex].
Thus, the correct answer is:
A. 3 or -3
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here,
[tex]\[ x_1 = -3, \][/tex]
[tex]\[ y_1 = k \][/tex]
[tex]\[ x_2 = 2, \][/tex]
[tex]\[ y_2 = 0 \][/tex]
[tex]\[ d = \sqrt{34} \][/tex]
We substitute the values into the distance formula:
[tex]\[ \sqrt{34} = \sqrt{(2 - (-3))^2 + (0 - k)^2} \][/tex]
Simplify inside the square root:
[tex]\[ \sqrt{34} = \sqrt{(2 + 3)^2 + (0 - k)^2} \][/tex]
[tex]\[ \sqrt{34} = \sqrt{5^2 + (-k)^2} \][/tex]
[tex]\[ \sqrt{34} = \sqrt{25 + k^2} \][/tex]
Next, remove the square roots by squaring both sides of the equation:
[tex]\[ 34 = 25 + k^2 \][/tex]
To isolate [tex]\( k^2 \)[/tex], subtract 25 from both sides:
[tex]\[ 34 - 25 = k^2 \][/tex]
[tex]\[ 9 = k^2 \][/tex]
Now, solve for [tex]\( k \)[/tex] by taking the square root of both sides:
[tex]\[ k = \pm \sqrt{9} \][/tex]
[tex]\[ k = \pm 3 \][/tex]
Therefore, the values of [tex]\( k \)[/tex] that satisfy the condition are [tex]\( k = 3 \)[/tex] and [tex]\( k = -3 \)[/tex].
Thus, the correct answer is:
A. 3 or -3
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.